Stereo vision–based non-contact dynamic measurement method for vehicle braking time sequence. (September 2019) - Zhang, Libin; Wu, Dao; Shan, Hongying; Zhang, Lele
The braking stability of semi-trailer train is directly related to the safety of driving. The braking time sequence of vehicle in braking process directly determines the braking stability of the vehicle. To overcome the limitations of the existing technology, this paper proposes a novel non-contact vehicle braking time sequence measurement method. The proposed method is based on binocular stereo vision that has high precision, high efficiency and low cost. First, the binocular stereo vision measurement principle is introduced, the camera is calibrated by three-dimensional target and the Levenberg–Marquardt algorithm is used to optimize the calibration parameters. Then, a series of image processing techniques are used to extract the wheel marker and perform three-dimensional coordinate reconstruction. Finally, the universality and the applicability of the proposed method are verified by conducting repetitive experiments and accuracy experiments for the same vehicle and different types of vehicles according to the designed experimental process and the established evaluation index. The experimental results show that the method proposed in this paper can achieve fast detection, with high accuracy and good repeatability. Moreover, the method can be extended to various types of vehicles.